Social Loss Corruption Cases in Indonesia: How Should the Corruptors Punished? - Nabila, Suci (Universitas Negeri Semarang (UNNES), 2019)
Corruption is a serious problem that occurs in a country including Indonesia. Corruption is a problem that has a very big impact on the country and causes a lot of losses that its handling has not been taken seriously. This crime is very difficult to eradicate, because it is usually carried out in a systematic way and involves the authorities or people who hold economic and political power. In various countries the way to punish perpetrators of corruption is very diverse. In Indonesia alone the punishment used is a sentence of imprisonment. But the sentence of confinement in Indonesia is considered to have a deterrent effect. It is appropriate for a corruptor to be given severe sanctions and give a deterrent effect, one of which is a death sentence. But in Indonesia there are pros and cons regarding this death sentence.